Money Check Result Data Management Application Section Verbasar By Web-Based (Case Study : Perum Peruri) (Buana Information Technology and Computer Sciences (BIT and CS), 2022)
The use of computer technology and information systems in the 20th century has been widely used, including companies. The advantage of using an information system in the company is that it can provide data management media in the company's business processes where it is very necessary for effectiveness to be achieved. The Verbasar section is one of the sections in Perum Peruri which is in charge of checking the printouts of banknotes, with around 100 employees. There are still problems in the management and storage of data on the results of money checks in the Verbasar Section. The problem is the use of Microsoft Excel as a media for data management and storage which is considered not optimal. Therefore, a web-based application for data management results from Verbasar Section money checks was built as a substitute for the old system so that data management and storage became more optimal in the process and reports. In making this application, researchers used data collection methods such as observation, interviews, and literature studies. SDLC (System Development Life Cycle) Waterfall model is used for system development method with UML (unified modeling language) as modeling tools to develop information system design. The expected result is that the management of money audit results data can provide a better system than the old system in terms of data management